Molecular investigation of Coxiella burnetii infections in aborted sheep in eastern Turkey - Kilic, A.; Kalender, H.; Koc, O.; Kilinc, U.; Irehan, B.; Berri, M. (Shiraz Univ, 2016)
Q fever is a zoonotic disease that occurs worldwide and is caused by the obligate intracellular bacterium Coxiella burnetii. The aim of this study was to investigate the presence of C. burnetii infection in aborted sheep in eastern Turkey using PCR. A total of 200 fetuses were collected from aborted sheep belonging to 200 herds in different locations in the eastern part of Turkey. Foetal organ samples such as liver, spleen, lung and stomach were taken and the DNA was purified from two hundred pooled samples. PCR analysis of C. burnetii presence in infected organs was performed, and 4 samples (2%) were found positive. In addition, the pooled organ suspensions were inoculated to embryonated chicken eggs, and PCR analysis of yolk sacs showed C. burnetii DNA in 5 samples (2.5%). This study shows that C. burnetii infection has an important role in sheep abortions in eastern Anatolia region.
Keywords: Abortion; Eastern Turkey; PCR; Q fever; Sheep